Tracing the Footsteps of Liku: Integration of the Penta Helix Model in Arja Art in Bali - Komang David Darmawan, David; Hartono; Purnomo, Sucipto Hadi (Terob : Jurnal Pengkajian dan Penciptaan Seni, 2025)
This research explores the role of the Liku figure in Arja art, as well as the application of the penta helix model to support the preservation and development of this art. Liku, as a humorous and passionate character, functions as a symbol of rebellion against social norms and creates dynamic interactions with the audience. Through a penta helix approach, which involves collaboration between historians, artists, communities, government and media, this research shows that Arja's artistic desires can be achieved by utilizing the strengths of each element. Qualitative research methods were used to collect data through direct observation and in-depth interviews with artists and community members. The research results reveal that the penta helix integration model not only strengthens the preservation of traditions but also creates space for the younger generation to be actively involved in the arts. Therefore, this article contributes to a deeper understanding of the dynamics of Arja performing arts in Bali and the importance of cross-sector collaboration in preserving cultural heritage. It is hoped that this research will provide insight for artists, historians and the general public regarding the relevance and adaptation of traditional art in the modern era.